Women's Participation in Simultaneous Village Head Elections in Bandung Regency - Endang Hermawan; Rini Sulastri (UIN Sunan Gunung Djati, 2023)
The simultaneous village head election in Bandung Regency in 2021 was attended by 194 male village head candidates and 13 female village head candidates. The lack of women running for village heads can be seen from the driving and inhibiting factors. This study aims to determine the driving factors and obstacles for women participating in the simultaneous election of the Village Head in Bandung Regency in 2021. A qualitative approach, the literature study method, was used in this study. The research data is sourced from journal articles that have been published and are available on Google Scholar. This study found that the factors driving women to participate in simultaneous Pilkades in Bandung Regency include: first, female village head candidates understood their political freedom. This can be seen in his participation in the candidacy for village head in the simultaneous Pilkades in 2021 in Bandung Regency; second, the education and abilities of women who continue to develop. This can be seen in female village head candidates' access to education and capabilities in the simultaneous 2021 Pilkades in Bandung Regency.